(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Psoriasis, a chronic immune-mediated inflammatory skin disease, affects 2-4% of the global population, with a higher prevalence in Western regions. While not fatal, psoriasis significantly impacts patients’ quality of life and is associated with an elevated risk of comorbidities, including diabetes, cancer, and cardiovascular illnesses. This review explores the epidemiological variations, genetic influences, and triggers contributing to psoriasis development. The gold standard for determining severity is the Psoriasis Area and Severity Index (PASI) score, guiding treatment decisions. Traditional treatments involve topical and systemic approaches, with topical corticosteroids being a cornerstone. However, recent advances have introduced Nanostructured Lipid Carriers (NLCs) as a promising drug delivery system for improved psoriasis treatment. NLCs offer advantages such as increased drug loading capacity, regulated release timelines, and extended shelf life. The review also discusses other lipid-based carriers, such as liposomes, transferosomes, and niosomes, along with metallic and polymeric nanoparticles, highlighting their potential in psoriasis management. Current treatment modalities aim to alleviate symptoms, but there is no cure for psoriasis. Future perspectives emphasize the potential of NLCs, calling for more clinical studies to validate their therapeutic efficacy and ensure safety. Collaboration among regulatory bodies is essential to establish guidelines for nano-formulation manufacturing. The evolving landscape signifies a promising era for personalized and efficient psoriasis management, leveraging innovative drug delivery systems to enhance treatment outcomes